Four new species of Plumachaetas Salmon (Collembola: Entomobryoidea) from Oceania with comments on the genus and a key to species - Oliveira, Fábio G. L.; Greenslade, Penelope; Bellini, Bruno Cavalcante (Zootaxa, 2019)
Plumachaetas Salmon is a genus of Entomobryoidea with 11 valid species, all from Oceania. The genus is characterised by the presence of lanceolate scales, the subapical chaeta of the maxillary outer lobe thick and blunt, dental spines absent and a short mucro. In this paper we describe four new species of Plumachaetas from Oceania: P. belae sp. nov., P. loriensis sp. nov., P. mamuensis sp. nov. and P. wanangensis sp. nov. Plumachaetas belae sp. nov. and P. mamuensis sp. nov. are similar to each other, and to P. queenslandica (Schött) and P. yoshii Zhang & Deharveng, but are unique in the combination of dorsal and labial chaetotaxy. Plumachaetas loriensis sp. nov. resembles P. halmaherae (Yoshii & Suhardjono) and P. sunae Zhang & Deharveng but differs in labial, dorsal chaetotaxy and unguiculus shape. Plumachaetas wanangensis sp. nov. is similar to other taxa bearing a mucro with four teeth, but presents a unique combination of macrochaetae on thoracic and abdominal segments. All species are arboreal and were collected in Malaise traps set in humid rainforests. A map of the geographic distribution and ecological remarks on the genus are provided and a key to species with a table summarising the main morphological features of all described taxa in the genus.